Transcendence in the Kinanthropology of Manuel Sérgio - Palma, Alexandre Coutinho Lopes de Brito (REVER: Revista de Estudos da Religião, 2020)
This article seeks to analyze the contribution of Portuguese philosopher Manuel Sérgio to Religious Studies. The author dedicated his long academic life to the study of sports, but with a peculiar humanistic perspective. Instead of focusing on performance, the author focuses on the Human being who moves. This is what he defines as “Kinanthropology”. Transcendence is a major element in this proposal. In this article, after presenting Sérgio’s fundamental anthropological framework and his understanding of “human kinetics”, three of his possible theoretical contributions to Religious Studies are explored: 1. in the way he sees the relation between transcendence and religion; 2. in the way he opens corporeity to transcendence; and 3. in the way he seems to rehabilitate motion as a topic for religious and theological discourse.